2007
DOI: 10.2754/avb200776010003
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, Blood and Rumen Chemistry Changes in Lambs Following Supplementation with Se-yeast

Abstract: Faixová, Z., ·. Faix, ª. Leng, P. Váczi, Z. Maková, R. Szabóová: Haematological, Blood and Rumen Chemistry Changes in Lambs Following Supplementation with Se-yeast. Acta Vet Brno 2007, 76: 3-8 The effects of feed supplementation with organic form of selenium (Se) on ruminal enzyme activities (ALT, AST, GGT, ALP and GDH), blood enzyme activity (GPx), serum enzyme activities (LDH, CK) and haematological indicators were examined in lambs. Ten animals were divided into two groups and fed experimental diets for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
5
19
5
Order By: Relevance
“…2) in lambs of both groups a er birth was at a lower level until day 10 if compared with day 30 and 60, when it increased signifi cantly (P < 0.05) in both groups of lambs and when group B of lambs had an insignifi cantly higher RBC count during the entire experiment. Similar results like in our experimental lambs were reported by Faixová et al (2007). On the other hand Soliman et al (2012) and Ocal et al (2013) reported a higher RBC count in lambs compared to the presented results.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2) in lambs of both groups a er birth was at a lower level until day 10 if compared with day 30 and 60, when it increased signifi cantly (P < 0.05) in both groups of lambs and when group B of lambs had an insignifi cantly higher RBC count during the entire experiment. Similar results like in our experimental lambs were reported by Faixová et al (2007). On the other hand Soliman et al (2012) and Ocal et al (2013) reported a higher RBC count in lambs compared to the presented results.…”
Section: Resultssupporting
confidence: 92%
“…It gradually decreased in both groups from day 1 to day 60 to the value of 6.60 μkat/l (P < 0.05) on day 60 a er birth in group A. The ALP activity of our lambs was higher than the values reported by Faixová et al (2007), Ouanes et al (2011) in lambs of mothers without increased iodine supplementation. Total protein concentration (Fig.…”
Section: Variablecontrasting
confidence: 55%
“…Our previous experiment showed that the total erythrocyte count was significantly higher in Se-yeast supplemented lambs than in the control group, and the total white blood cell count was significantly higher in the control group than in the Se-yeast supplemented group (Faixová et al 2007). According to literature, selenium is essential in regulating haematopoiesis by differentiation of erythroid progenitors of C57/BL6 mice (Kaushal et al 2011).…”
Section: Rumen Blood Enzymes Ruminantmentioning
confidence: 87%
“…3 mg Se/kg of DM compared to the group given basal diet (Faixová et al 2007). Mihaliková et al (2005) reported that selenomethionine has a protective effect on the growth of some protozoa species in young ruminants.…”
Section: Rumen Blood Enzymes Ruminantmentioning
confidence: 99%
“…Since the main precursors of milk fat originate in the rumen, the increased milk fat content may have been influenced by rumen fermentation. The effect of Se supplementation in the form of yeast on the rumen fermentation was studied by Faixová et al (2007). They found significantly higher activity of alkaline phosphatase and glutamate dehydrogenase in ruminal fluid in Se-supplemented group.…”
Section: Discussionmentioning
confidence: 99%